Choice awareness and manipulation blindness: A cognitive semiotic exploration of choice-making - Mouratidou, Alexandra (Public Journal of Semiotics, 2020)
Within cognitive science, “blindness” to choice is commonly treated as typical of human cognition, implying unreliable agents who essentially lack any awareness of their own choices (e.g. Johansson et al., 2005, 2008; Hall et al., 2010, 2013). Within cognitive semiotics, however, choice awareness is seen as a continuous phenomenon, which is susceptible to the influence of a variety of factors. Manipulation blindness is proposed as a more adequate term for what is known in the literature as “choice blindness”, referring to participants’ tendency to accept a choice as if it were their own. This suggests that “blindness” is strictly limited to the level of detection (of the switch of the preferred choice to a non-chosen one), and not to the level of choice. Using a cognitive-semiotic framework, I examine manipulation blindness as an “indicator” of choice awareness by employing the factors of memory, consequence, and affectivity, and introduce a two-level hierarchy of choice-making. 43 participants were assigned two tasks combining choices with a) two degrees of consequence (more/less) – based on task instructions, and b) two degrees of affectivity (high/low) – based on stimuli with different degrees of abstractness. Participants were first asked to state their preference for one of two alternatives (choice) . After that they were shown chosen as well as non-chosen pictures and asked to confirm whether the picture presented was the one of their choice (memory). Lastly, they were asked to justify their choice, although some of the trials had been manipulated (i.e. the chosen card was switched with the non-chosen one) (manipulation) . Half of the manipulations were detected, and 75% of these detections occurred for the choices participants remembered correctly. While the consequential impact of the choice did not seem to influence detection, affectivity did. Unlike other experiments that investigate “choice blindness”, the results indicate that manipulation blindness is subject to memory and affectivity, suggesting that we are aware of our choices and that we have, to various degrees, access to our intentional acts.